2022
DOI: 10.1007/s40618-021-01719-w
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between hyperuricemia with deposition and sexual dysfunction in males and females

Abstract: Purpose The association between gout, the most common crystal arthropathy, and sexual dysfunctions has often been investigated by studies in the last decades. Despite the presence of shared risk factors and comorbidities and the possible effects on sexual health of long-term gout complications, awareness of this association is severely lacking and the pathogenetic mechanisms have only partially been identified. In the present review, we aimed to investigate the current evidence regarding the poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 173 publications
0
3
0
Order By: Relevance
“…The common complications of GA include cardiovascular diseases, 38,39 diabetes, 40 renal function impairment, 41 sexual dysfunction, 42 and ophthalmic diseases. 43 Recent studies have found that NLR may be able to predict the risk and outcome of GA comorbidities.…”
Section: Nlr and Ga Comorbiditiesmentioning
confidence: 99%
“…The common complications of GA include cardiovascular diseases, 38,39 diabetes, 40 renal function impairment, 41 sexual dysfunction, 42 and ophthalmic diseases. 43 Recent studies have found that NLR may be able to predict the risk and outcome of GA comorbidities.…”
Section: Nlr and Ga Comorbiditiesmentioning
confidence: 99%
“…During hyperuricemia or gout attacks, UA crystals accumulate in blood vessels and the joints to trigger in ammation responses. Then this in ammation response can contribute to the occurrence of ED 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Having gout there is a 20% increased risk of developing ED, even after adjusting for possible confounders, including comorbidities. Considering that hyperuricemia is the underlying condition favoring gout development and that hyperuricemia is associated with endothelial dysfunction and CVD [ 74 ], it is obvious that known or even unknown comorbidities might favor ED development [ 75 ]. Finally, the couple, being in a stable relationship, may have a positive “anti-inflammatory” role in modifying incorrect lifestyles leading to gout and to other metabolic risk factors producing ED [ 76 ].…”
Section: Methodsmentioning
confidence: 99%